The interplay of past consumption, attitudes and personal norms in organic food buying. (1st June 2019) - Koklic, Mateja Kos; Golob, Urša; Podnar, Klement; Zabkar, Vesna
Abstract: Our society has been marked by mounting discourses on the necessity of sustainable and environmentally friendly food consumption, as sustainability problems regarding food systems will likely become more severe in the future. Hence, calls have been made for more research on consumer behavior with respect to organic food consumption. Using a survey of 462 adults in a European Union country, this study investigates the role of past behavior in determining several consequences in the context of organic food consumption. The relationships among past organic food consumption, attitudes, environmental concern, personal norms and organic food buying intentions are examined. The results reveal that past organic food consumption positively affects attitudes toward buying organic food, personal norms and buying intentions. In addition to past consumption, attitudes and personal norms are also significant antecedents of organic food buying intentions. The total effect of past behavior on the intention is the strongest compared to other antecedents. The study also discusses the implications of the findings and identifies areas for future research.